Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Acclimation of bloom‐forming and perennial seaweeds to elevated p CO 2 conserved across levels of environmental complexity - Dong Xu; Charlotte‐Elisa Schaum; Fan Lin; Ke Sun; James R. Munroe; Xiao W. Zhang; Xiao Fan; Lin H. Teng; Yi T. Wang; Zhi M. Zhuang; Naihao Ye (Global Change Biology, 2017)
Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO 2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO 2 levels ranging from 400 to 2,000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO 2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds.

Experimental Investigation of the Anisotropic Mechanical Properties of a Columnar Jointed Rock Mass: Observations from Laboratory-Based Physical Modelling - H. Ji; J. C. Zhang; W. Y. Xu; R. B. Wang; H. L. Wang; L. Yan; Z. N. Lin (Rock Mechanics and Rock Engineering, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)